Virtual bound states elements and their effects on magnetic and electrical properties of Fe-Ni based metal amorphous nanocomposites. (August 2019) - Aronhime, N.; Ohodnicki, P.; McHenry, M.E.
Abstract: Metal amorphous nanocomposite alloys, with compositions (Fe70 Ni30 )80-x Nb4 Si2 B14 TEx (0 ≤ x ≤ 5), where TE is a transition element, and (Fe70 Ni30 )80-y Nb4+y Si2 B14 (0.5 ≤ y ≤ 2) were synthesized. Samples were annealed at 440 °C and strain-annealed at 440 °C and 300 MPa. Resistivity was found to increase with small substitutions of TE elements. Increasing V resulted in reduced Bs from 1.2 T to 0.5 T. Further Mo additions lowered Bs to 0.6 T, and consistently reduced the permeability. For Cr and Nb, resistivity increased, and strain-annealed permeability was lower than the annealed permeability. Lastly, toroidal core losses on (Fe70 Ni30 )79.5 Nb4 Si2 B14 V1 yielded W1.0/400 = 2.1 W/kg, and W1.0/1 k = 6.0 W/kg. Graphical abstract: Unlabelled Image